From Regulation to Practice: Implementing Regulation No. 46 of 2018 on Child Marriage Prevention in Lais District, Musi Banyuasin Regency - Ariska, Ariska; Laraskana, Tiara Nesva; Hestiriniah, Deby Chintia; Pusnita, Indah; Santoso, Budi (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Despite sustained regulatory efforts, child marriage remains highly prevalent in Musi Banyuasin Regency, particularly in Lais District, making it a critical context for assessing the effectiveness of child marriage prevention policies. In response to this issue, the Regency Government enacted a regulation aimed at reducing child marriage in Lais District; however, the outcomes of its implementation remain problematic. This study examines the implementation of the child marriage prevention policy in Lais District using a qualitative research design. Data were collected through in-depth interviews, field observations, and document analysis. The findings reveal that policy implementation has not yet been effective, despite the regulation being formally enacted. Key challenges include weak coordination among implementing actors, limited human resource capacity, social resistance, and the persistence of harmful socio-cultural practices. At the same time, positive initiatives have been undertaken by the Office of Religious Affairs (KUA), local communities, and village governments through education and socialization programs. Nevertheless, these efforts face significant constraints and have not yet produced substantial change. The study underscores the need for stronger community empowerment and increased public education on the negative consequences of early marriage. This research contributes to the literature on public policy implementation and provides practical insights for policymakers and community stakeholders seeking to strengthen child marriage prevention efforts.